2009
DOI: 10.4103/0970-9290.57375
|View full text |Cite
|
Sign up to set email alerts
|

Oral lichen planus versus oral lichenoid reaction: Difficulties in the diagnosis

Abstract: Lichen planus (LP) is a mucocutaneous disease with well-established clinical and microscopic features. The oral mucosa and skin may present clinical and microscopic alterations similar to those observed in LP, called lichenoid reactions (LRs), which are triggered by systemic or topical etiological agents. The difficulties faced to establish the differential diagnosis between the two pathologies were investigated in the literature. It was observed that the etiology of LP is still under discussion, with a tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 39 publications
0
54
0
2
Order By: Relevance
“…Oral lichenoid drug reaction which cause by various drugs such as Allopurinol, Carbamazepine, Chloroquine, Dapsone, Ketoconazole, NSAIDs, Propanolol, Tetracycline. 3,4 The most reliability in diagnosis of OLDR is to see the lesion resolution after withdrawal of the suspected drugs, and the reaction may recur when the patient is rechallenged with the same drug. Oral lichenoid lesion (s) of graft-versushost disease (OLL-GVHD).…”
Section: Introductionmentioning
confidence: 99%
“…Oral lichenoid drug reaction which cause by various drugs such as Allopurinol, Carbamazepine, Chloroquine, Dapsone, Ketoconazole, NSAIDs, Propanolol, Tetracycline. 3,4 The most reliability in diagnosis of OLDR is to see the lesion resolution after withdrawal of the suspected drugs, and the reaction may recur when the patient is rechallenged with the same drug. Oral lichenoid lesion (s) of graft-versushost disease (OLL-GVHD).…”
Section: Introductionmentioning
confidence: 99%
“…This might explain the higher frequency of OLPs and OLRs in the buccal mucosa, tongue, and gingiva (33)(34)(35). Additionally, Holmstrup et al found that local factors such as dental plaque and calculus worsen gingival OLPs (36).…”
Section: Discussionmentioning
confidence: 99%
“…[1920] Whereas restorative dental materials play an important role in the appearance of OLR,[21] and many studies have documented contact hypersensitivity to dental materials such as amalgam,[22] composite[23] and dental acrylics. [24] Additionally, other conditions such as lupus erythematosus, erythroleukoplakia, leukoplakia, and proliferative verrucous leukoplakia may present clinical and histopathology characteristics similar to oral lichen planus.…”
Section: Introductionmentioning
confidence: 99%